Mathematical Modeling of Solar Cabinet Dryer to Predict its Temperature - Sharma, P K (Journal of Agricultural Engineering, 2009)
A simple mathematical model to predict the hourly average crop and air temperatures in a cabinet dryer has been presented with ambient temperature and solar intensity as the input parameters. The model predictions have been compared with the experimental data for a day. The model could be used to study the effects of cabinet dryer and crop parameters on dryer performance at a given location.